Ergovaline occurrence in grasses infected by fungal endophytes of semi-arid pastures in Spain - Vazquez de Aldana, Beatriz R.; Zabalgogeazcoa, Iigo; Garcia Ciudad, Antonia; Garcia Criado, Balbino (Journal of the Science of Food and Agriculture, 2003)
: Ergovaline is a mycotoxin produced by fungal endophytes belonging to Neotyphodium and Epichloe¨ spp in several host grass species. Owing to the production of this alkaloid, the ingestion of endophyte-infected grasses causes toxicosis in grazing animals. The aim of this work was to determine if ergovaline is produced in several grasses (Agrostis castellana Boiss and Reuter, Brachypodium phoenicoides (L) Roemer and Schultes, Dactylis glomerata L, Festuca arundinacea Schreb, Festuca arundinacea Schreb subsp fenas (Lag) Arcangeli, Festuca ovina L, Festuca rubra L, Holcus lanatus L and Lolium perenne L) infected by fungal endophytes in ‘dehesa’ pastures in Spain. Forage and seed samples of several ecotypes of these grass species were analysed for their ergovaline content by HPLC with ﬂuorescence detection. The ergovaline content ranged between 0.03 and 0.85mg g 1 in forage and 0.28 and 3.17mg g 1 in seed samples of F arundinacea, between 0.00 and 0.08mg g 1 in forage and 0.02 and 0.19mg g 1 in seed samples of F rubra, between 0.00 and 0.02mg g 1 in forage samples of H lanatus, and was 0.11mg g 1 in one ecotype of F ovina. All nine ecotypes of F rubra had ergovaline in seed samples, but in three ecotypes the alkaloid was not detected in forage samples. No ergovaline was detected in the other four endophyte-infected grasses analysed. The ergovaline content should be considered as an anti-quality parameter to be measured when the nutritional quality of these pastures is evaluated
Keywords: dehesa grasslands; endophytes; epichloe; ergovaline; mycotoxins; neotyphodium

Ergovaline occurrence in grasses infected by fungal endophytes of semi-arid pastures in Spain (Journal of the Science of Food and Agriculture, 2003)
: Ergovaline is a mycotoxin produced by fungal endophytes belonging to Neotyphodium and Epichloe¨ spp in several host grass species. Owing to the production of this alkaloid, the ingestion of endophyte-infected grasses causes toxicosis in grazing animals. The aim of this work was to determine if ergovaline is produced in several grasses (Agrostis castellana Boiss and Reuter, Brachypodium phoenicoides (L) Roemer and Schultes, Dactylis glomerata L, Festuca arundinacea Schreb, Festuca arundinacea Schreb subsp fenas (Lag) Arcangeli, Festuca ovina L, Festuca rubra L, Holcus lanatus L and Lolium perenne L) infected by fungal endophytes in ‘dehesa’ pastures in Spain. Forage and seed samples of several ecotypes of these grass species were analysed for their ergovaline content by HPLC with ﬂuorescence detection. The ergovaline content ranged between 0.03 and 0.85mg g 1 in forage and 0.28 and 3.17mg g 1 in seed samples of F arundinacea, between 0.00 and 0.08mg g 1 in forage and 0.02 and 0.19mg g 1 in seed samples of F rubra, between 0.00 and 0.02mg g 1 in forage samples of H lanatus, and was 0.11mg g 1 in one ecotype of F ovina. All nine ecotypes of F rubra had ergovaline in seed samples, but in three ecotypes the alkaloid was not detected in forage samples. No ergovaline was detected in the other four endophyte-infected grasses analysed. The ergovaline content should be considered as an anti-quality parameter to be measured when the nutritional quality of these pastures is evaluated